Supply of public transport connections to commuters in the region of Wrocław - a quantitative analysis - Małysz, Michał; Kierzkowska, Anna (Bulletin of Geography. Socio-economic Series, 2026)
Aim. Wrocław, as a regional centre, impacts many municipalities in the Lower Silesian Voivodeship and neighbouring voivodeships. One measure of such connections is the daily commute to work or school from the residence to the city. Organising sustainable mobility and responding to the existing demand is a significant challenge for local and regional policy. The study aims to define the level of supply of public transport connections in the region of daily commutes to Wrocław concerning the estimated demand for commuting. Results and conclusions. The study includes data analysis obtained from the 2021 National Census, research made using the original RTCP indicator, and classifications of research units given demand and supply. This allowed us to notice some units with insufficient supply to meet demand. Exemplary solutions were developed for the diagnosed challenges using PTV Visum transport planning software.